965 Complication Rates in Operatively Managed Ankle Fracture/Dislocations - The Effect of Pre-Reduction Imaging and Compliance with BOAST 12 Guidance. (12th October 2021) - Phoon, K M; Ward, A; O'Dowd, D; Pitcher, F; Amos, L; Butler, J; Brewer, P; Davies, M; Chadwick, C; Davies, H; Blundell, C
Abstract: Aim: The BOAST-12 guidelines for the management of ankle fractures aims to optimise functional recovery and reduce complications. They advise against having radiographs prior to urgent reduction of clinically deformed ankles as it could cause an unacceptable delay to subsequent management. Our study aimed to assess the effect of time to acceptable reduction on the risk of complications and time to definitive reduction. Method: This was a retrospective observational study of patients with ankle fracture-dislocations between 2013 to 2017 at the Northern General Hospital's Emergency Department (ED). Information collected from 2 patient groups (with and without pre-reduction radiographs), included patient demographics, time to accepted reduction, number of manipulations, operations, and subsequent complications. Results: 242 patients were identified. Time from arrival in ED to acceptable reduction was significantly longer in patients with pre-reduction radiographs versus patients without (184.5 vs 82 minutes, p < 0.00), but did not increase the overall risk of complications (p = 0.62). Pre-reduction radiographs were associated with insignificantly higher rates of post-traumatic osteoarthritis (p = 0.17) and slightly longer wait time for definitive intervention (1 vs 2 days, p = 0.72). However, this had no relationship with the number of manipulations (p = 0.53). Conclusions: The use of pre-reduction radiographs significantly increased time to acceptable reduction of ankle fracture-dislocations. However, this was not associated with increased risk of complications or time to definitive management.